Partner Support with Condom Use Consistency in Transmission Prevention of People with HIV AIDS - Nirwanto K Rahim; Rosmin Ilham; Yuniar Mansye Soeli; Kevin Efrain Tololiu (Jambura Nursing Journal, 2023)
HIV remains a public concern with an increasing prevalence. HIV prevention can be done by considering the ABC approach; Abstinence (A), Be faithful (B), and Correct and consistent condoms (C). Globally, the use of condoms is still one of the HIV prevention interventions. However, this intervention is often overlooked, leading to inconsistent condom use. This study aimed to investigate the relationship between partner support and the consistency of condom use. This study used a cross-sectional method in Rumah Singgah Dukungan Teman Sebaya, Gorontalo City. The calculation of the Chi-square test revealed a p-value of 0.008 (p ˂ 0.05). This finding indicates a significant relationship between partner support and the consistency of condom use at Rumah Singgah Dukungan Teman Sebaya, Gorontalo City.